2019
DOI: 10.3390/met9121250
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Complex Zygomatic Bone Defects Using Mirroring Coupled with EBM Fabrication of Titanium Implant

Abstract: Reconstruction of zygomatic complex defects is a surgical challenge, owing to the accurate restoration of structural symmetry as well as facial projection. Generally, there are many available techniques for zygomatic reconstruction, but they hardly achieve aesthetic and functional properties. To our knowledge, there is no such study on zygomatic titanium bone reconstruction, which involves the complete steps from patient computed tomography scan to the fabrication of titanium zygomatic implant and evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Metals 2020, 9, x FOR PEER REVIEW 2 of 31 0.7 mm. Moiduddin et al obtained a titanium zygomatic implant with the EBM technique, using Ti-6Al-4V ELI (extra low interstitial) powder [144]. The same author [145] compared different kinds of Ti-6Al-4V ELI mandibular implants for goats: EBM plate with mesh, EBM titanium plate without mesh and a commercial reconstruction plate.…”
Section: Maxillofacial Implantsmentioning
confidence: 99%
“…Metals 2020, 9, x FOR PEER REVIEW 2 of 31 0.7 mm. Moiduddin et al obtained a titanium zygomatic implant with the EBM technique, using Ti-6Al-4V ELI (extra low interstitial) powder [144]. The same author [145] compared different kinds of Ti-6Al-4V ELI mandibular implants for goats: EBM plate with mesh, EBM titanium plate without mesh and a commercial reconstruction plate.…”
Section: Maxillofacial Implantsmentioning
confidence: 99%
“…The material was evaluated as a potential prosthetic biomaterial used for cortical bone replacement and compared with commercial, pure Ti used for bone replacement implants. Moiduddin et al [16] proposed an integrated system methodology for the reconstruction of complex zygomatic bone defects, using Ti-6Al-4V ELI alloy, comprising several steps, right from the patient scan to implant fabrication, while maintaining proper aesthetic and facial symmetry. Finally, it was concluded that a mirror-designed titanium implant (fabricated by the electron beam melting method) satisfies the aesthetic, functional, and mechanical properties for efficient zygomatic bone reconstruction.…”
Section: Special Applications and Technologiesmentioning
confidence: 99%
“…Titanium alloy (Ti 6Al 4V), nickel alloy (Inconel 718), and aluminum alloy (AA 2024) are widely used materials in various engineering applications such as biomedical implants, aerospace, ship building, automotive, and many more as reported by Lupi et al [ 1 ], Nalli et al [ 2 ], and Wang et al [ 3 ]. The production of these materials in the form of near-net-shape products is extensively carried out through several means, especially selective laser melting (SLM) as adopted by Fan and Feng [ 4 ], and electron beam melting (EBM) used by Moiduddin et al [ 5 ]. The surface roughness of these produced alloys through the said processes is experienced to be very high.…”
Section: Introductionmentioning
confidence: 99%